State-specific prevalence of current e-cigarette use by disability status and disability type—United States, BRFSS 2016–2018. Issue 1 (January 2022) - Zhang, Qing C.; Courtney-Long, Elizabeth A.; Sinclair, Lisa B.; Reese, Sierra; Armour, Brian S.; Shapira, Stuart K.
Abstract: Background: Cigarette smoking is the leading cause of preventable disease and death in the United States. The tobacco product landscape has diversified to include electronic cigarettes (e-cigarettes). Adults with disabilities are more likely than adults without disabilities to smoke cigarettes, but within the current body of literature, there is limited information on the use of e-cigarettes among adults with disabilities. Objective: To assess overall and state-specific prevalence of current e-cigarette use among adults by disability status, disability type, sex, and age. Methods: Disability was defined as having serious difficulty with vision, hearing, mobility, cognition, or any difficulty with self-care or independent living. The Behavioral Risk Factor Surveillance System cross-sectional survey data (2016–2018; n = 1, 150, 775) were used to estimate state and District of Columbia prevalence of current e-cigarette use among adults (aged ≥18 years) with and without disabilities, overall and by disability type, sex, and age group. Results: Median prevalence of current e-cigarette use was higher among adults with than without disabilities (6.5% vs. 4.3%, P < 0.05). Among adults with disabilities, use varied from 2.5% in DC to 10.0% in Colorado; median use was highest among those with cognitive disabilities (10.0%) and those aged 18–24 years (18.7%). Conclusions: Prevalence of current e-cigarette use was higher among adults with than without disabilities and varied across states by disability status, type, and age group. The findings underscore the need to monitor e-cigarette use among adults with disabilities and specifically include them in tobacco control policies and programs addressing e-cigarette use.